The Lights and Shadows of Family Involvement in Small and Medium Sized Firms - Perez-Luno, Ana (My University, 2024)
This study analyzes the influence of human capital (HC) and altruism on small- and medium-size firms’ (SMEs) performance, contingent upon the effect of family involvement in management. HC, understood as the abilities, skills, and knowledge of firm personnel, has been proved to contribute to firm performance. Even more, firms’ outcomes benefit from aptitudes and also from attitudes, such as altruism. What is not so clear is if having a family character enhances the effect of HC and altruism on firm performance. Our results show that family involvement in management presents lights and shadows in its ability to extract all the potential of HC and altruism. By moving one-step forward in understanding these relationships, our findings contribute to the Family Firm, Human Resources Management, and Resource-Based View literatures.
PUBLISHED
Keywords: Family firms; Family involvement; Human capital; Firm performance; Inclusive Society; Human Resource Management; Leadership